Accruing genetic gain in pro-vitamin A enrichment from harnessing diverse maize germplasm - Menkir, A.; Maziya-Dixon, B.B.; Mengesha, W.; Rocheford, T.; Alamu, Emmanuel Oladeji (Springer, 2017)
Maize has been targeted as one of the major crops for provitamin enrichment and delivery because it is an inexpensive and easily available source of food for millions of people in sub-Saharan Africa. Although tropical-adapted yellow maize contains provitamin-A carotenoids that can be converted into vitamin A in the human body, they represent less than 25% of the total carotenoids in most widely grown and consumed maize cultivars in Africa. Novel genes conditioning high concentration of β-carotene and other carotenoids were then continually introduced from the temperate zone and tropics to boost provitamin A in tropical-adapted maize. Several promising inbred lines developed from backcrosses involving diverse exotic donor lines displayed provitamin A concentrations that match or surpass the current breeding target of 15 μg g−1. Some of these lines attained high provitamin A content by accumulating mainly high β-carotene while others contained high provitamin A by promoting accumulation of high levels of both carotenes and xanthophylls. Several inbred lines with intermediate to high levels of provitamin A have already been used to develop hybrids and synthetics without compromising grain yield and other adaptive traits that are required to profitably cultivate maize by farmers in West and Central Africa.